Expanding the Frontiers of Telecom Markets Through PPP in Peru - Stephens, Robert; Bossio, Jorge; Ngo, Jean-Christophe (World Bank, Washington, DC, 2012)
To help bring telephone service closer to Peru's poorest and most isolated areas, where people still had to travel some 56 kilometers on average to reach a pay phone, a pioneering fund offered subsidies to attract investment by private operators. Initial efforts led to impressive achievements, though slow implementation left room for improvement. A Public-Private Infrastructure Advisory Facility (PPIAF)-funded assessment of the first projects helped design the next generation of initiatives-and pointed to lessons for other developing countries. This paper list the following lessons: Governments should set measurable and achievable goals for a time frame of two to four years for their universal access programs, periodically updating the goals as they are met and as markets and technology evolve; universal access funds can be most effective and sustainable if they create incentives for private provision of services on a commercial basis.; imposing a 1-2 percent assessment on operators' revenues is an effective and transparent mechanism for financing universal access funds; making the universal access program part of the sector regulator, rather than a stand-alone agency or a line ministry, reduces political interference in the use of funds and makes it easier to introduce critical regulatory changes to support the program; sound regulatory measures can support universal access; output-based aid (OBA) subsidies are an effective use of universal access funds because they attract significant additional private investment; and governments should find ways to ensure that universal access funds are used in a timely way.